Synthesis and catalytic activity of silver- reduced graphene oxide and silver- magnetite- reduced graphene oxide nanocomposites in the reduction of 4-nitrophenol - Bahareh Kabiri; Hannaneh Heidari (Scientific Reports)
Abstract The catalytic reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) is vital for environmental remediation. This study synthesizes and assesses silver-reduced graphene oxide (Ag/rGO) and silver-magnetite-reduced graphene oxide (Ag/Fe2O4/rGO) nanocomposites for 4-NP reduction. Various reducing agents—ascorbic acid (AA), hydrazine hydrate (HH), sodium borohydride (SBH), and cellulose nanofibers (NFC)—were employed under reflux (R), hydrothermal (H), and ultrasonic (U) conditions. Drying methods (oven-drying (O) and freeze-drying (F)) and CTAB as a stabilizer were explored to optimize Ag NP distribution. The nanocomposites were characterized using FT-IR, XRD, FE-SEM, EDS, TEM, BET, TGA, ICP-OES, and VSM. XRD confirmed Ag NP formation with crystallite sizes of 12–23 nm. FE-SEM and TEM showed uniform distribution of cubic Fe2O4 and spherical Ag NPs (approximately 50 nm) on GO. The Ag/Fe2O4/rGO(O)-AA-U-F nanocomposite demonstrated the highest catalytic activity, with a pseudo-first-order rate constant (k) of 1.81 min−1 and a specific activity parameter (k') of 180.77 min−1.g−1. This nanocomposite exhibited a mesoporous structure with a high specific surface area (226.9 m2/g) and uniform Ag and Fe2O4 nanoparticle distribution on rGO. The combination of ascorbic acid (AA) and freeze-drying (F) yielded nanocomposites with superior catalytic performance due to their porous structure and uniform nanoparticle dispersion.